2009
DOI: 10.1007/s00417-009-1079-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of transcutaneous electrical simulation to improve recovery from corneal hypoesthesia after LASIK

Abstract: Transcutaneous electrical stimulation significantly improves corneal sensitivity at 3 months after LASIK. This may be due to accelerated corneal nerve regeneration by electrical stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…While no studies have reported on an ICT modality for ocular pain, we found four reports describing the use of TENS in the setting of ocular pathology and two that studied the effects of TENS in ocular pain (33)(34)(35)(36). Although the latter two reported pain relief, the first of these investigated the more invasive subcutaneous application of electrical current and the second from 1991 involved only ten cases in the setting of acute surgical pain (33,34).…”
Section: Introductionmentioning
confidence: 99%
“…While no studies have reported on an ICT modality for ocular pain, we found four reports describing the use of TENS in the setting of ocular pathology and two that studied the effects of TENS in ocular pain (33)(34)(35)(36). Although the latter two reported pain relief, the first of these investigated the more invasive subcutaneous application of electrical current and the second from 1991 involved only ten cases in the setting of acute surgical pain (33,34).…”
Section: Introductionmentioning
confidence: 99%
“…They applied electrical stimulation of continuous 20-Hz rectangular, biphasic wave pulses for 60 minutes. 30 Corneal sensitivity was significantly improved in comparison with the control group at 3 months after surgery (32 ± 13 mm improvement). 30 This is consistent with the findings of improved corneal sensitivity in the groups applied with 2-Hz and 20-Hz electrical stimulations in this study.…”
Section: Discussionmentioning
confidence: 82%
“… 28 , 29 In particular, Ghaffariyeh et al reported that transcutaneous electrical stimulation (TES) improved recovery of corneal nerve sensitivity at 3 months after surgery. 30 It could be suggested that the corneal nerve regeneration was accelerated by electrical stimulation. Although the functional recovery of the corneal nerves by electrical stimulation has been revealed, the structural recovery of the corneal nerves and the physiological mechanism by which electrical stimulation acts on corneal nerve recovery have not yet been revealed.…”
Section: Introductionmentioning
confidence: 99%
“…It is a non-invasive form of neuromodulation that has demonstrated effectiveness in numerous pain conditions and has been widely used over recent decades (12)(13)(14)(15). TES also has been used for treating ocular diseases with promising results (7,16,17).…”
Section: Introductionmentioning
confidence: 99%